2016
DOI: 10.1124/jpet.116.234765
|View full text |Cite
|
Sign up to set email alerts
|

CS-3150, a Novel Nonsteroidal Mineralocorticoid Receptor Antagonist, Shows Preventive and Therapeutic Effects On Renal Injury in Deoxycorticosterone Acetate/Salt-Induced Hypertensive Rats

Abstract: The present study was designed to assess both preventive and therapeutic effects of (S)-1-(2-Hydroxyethyl)-4-methyl-N-[4-(methylsulfonyl) phenyl]-5-[2-(trifluoromethyl) phenyl]-1H-pyrrole-3-carboxamide (CS-3150), a novel nonsteroidal mineralocorticoid receptor antagonist, on renal injury in deoxycorticosterone acetate (DOCA)/salt-induced hypertensive rats (DOCA rats). From 7 weeks of age, DOCA was subcutaneously administered once a week for 4 weeks to uninephrectomized rats fed a high-salt diet. In experiment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 52 publications
1
39
0
Order By: Relevance
“…Esaxerenone is a nonsteroidal mineralocorticoid receptor blocker that has exhibited kidney protective effects superior to eplerenone in preclinical trials (16,17). This study showed that esaxerenone as add-on therapy to RASi in Japanese participants for 12 weeks reduced UACR by approximately one half in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Esaxerenone is a nonsteroidal mineralocorticoid receptor blocker that has exhibited kidney protective effects superior to eplerenone in preclinical trials (16,17). This study showed that esaxerenone as add-on therapy to RASi in Japanese participants for 12 weeks reduced UACR by approximately one half in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 77%
“…Esaxerenone (CS-3150; Daiichi-Sankyo), a nonsteroidal mineralocorticoid receptor blocker, showed kidney protective effects in preclinical studies and may be added to existing treatments for patients with diabetic kidney disease (16,17). In a phase 1 study, the safety of a single dose and multiple doses of esaxerenone was confirmed in healthy Japanese subjects (18).…”
Section: Introductionmentioning
confidence: 99%
“…2015 b ). Furthermore, esaxerenone not only prevented but also ameliorated hypertension and renal injury in DOCA rats (Arai et al 2016). …”
Section: Non-steroidal Mras (The Recent 15 Years Of Mra Randd)mentioning
confidence: 99%
“…67 The effect of endothelial EnNaC deletion in promoting better recovery from hypoxia may be related to the increased generation of NO, thus preventing sustained vasoconstriction and allowing better kidney perfusion. [77][78][79] In a similar model, which uses DOCA administration instead of aldosterone, specific MR deletion in the endothelium ameliorated cardiac remodelling, but not renal injury, suggesting that the MR in the endothelium is not directly involved in this type of kidney injury and that other cell types in which the MR is expressed, such as inflammatory smooth muscle cells, must be involved. 67 Kidney fibrosis has been widely studied in the 5/6 nephrectomy model, in which aldosterone has shown to play a key role.…”
Section: Mrs In Kidney Injurymentioning
confidence: 99%
“…76 A similar benefit was observed in this model of aldosterone-induced kidney injury using novel non-steroidal MRAs, such as SM-368229 CS-3150 or AZD9977. [77][78][79] In a similar model, which uses DOCA administration instead of aldosterone, specific MR deletion in the endothelium ameliorated cardiac remodelling, but not renal injury, suggesting that the MR in the endothelium is not directly involved in this type of kidney injury and that other cell types in which the MR is expressed, such as inflammatory smooth muscle cells, must be involved. 52 The extent of MR-induced kidney injury differs between the various models of hypertension.…”
Section: Mrs In Kidney Injurymentioning
confidence: 99%